MANEJO DA COBERTURA DO SOLO EM POMAR DE PEREIRAS CV. HOSUI: EFEITOS NO SOLO, NUTRIÇÃO E CRESCIMENTO DAS PLANTAS E OCORRÊNCIA DE PLANTAS DANINHAS - Delonzek, Edina Costa (2017)
The present research aims to evaluate the effect of different kinds of mulch in the control of spontaneous plants and in the development of the „Hosui‟ pear tree. The experiment was conducted in an area in Cruz Machado/ PR, during the harvest of 2016 and 2017. The orchard was introduced in October 2015 with a Hosui‟ pear tree grafted onto a rootstock Pyrus calleriana. The experimental design was in randomized blocks, with seven treatments and four repetitions and experimental parts constituted by four plants. The treatments were: 1) witness (without cover), 2-) ryegrass (Lolium multiflorum) 3-)wooden dust, and millet (Pennisetum glaucum), 4-)shading material (70%), 5-) coverages of the soil with mulch of rice husk 6-) fiber of „curauá‟ (ananás erectifolius) and 7-) weeding (always clean). There were accomplished the following evaluations: Floristic data of the weed, pear tree vegetative growth, soil temperature and faunistic composition, soil chemical characteristics and nutritional status of pear trees. The results indicated that the coverings with curauá fiber or ryegrass straw + millet had higher suppression effects on the weeds and higher soil content of some mineral elements such as phosphorus and zinc. There was also interference of the coverings with pine sawdust and the natural cover showing lower heights and diameter of the pear trees. The coverings also influenced the soil temperature, on the other hand in the treatment with weeding, the soil was maintained with higher temperature in the measurements performed in the hours of 7:30 a.m and 12:30 p.m. The highest densities of organisms of the edaphic fauna were found in the coverings with rice husk and straw of ryegrass + millet. The foliar analysis showed levels of Mg and Mn at deficient levels for all the treatments.